1985
DOI: 10.3168/jds.s0022-0302(85)80880-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Milking Frequency on Productive and Reproductive Efficiencies of Dairy Cows

Abstract: Thirty-four mature Holstein cows were blocked into two groups on their 305-day, twice daily milked, mature equivalent milk production of the previous lactation; groups were assigned at random to a twice or thrice daily milking frequency. In addition, six pairs of paternal half-sisters and one pair of nonsibling heifers also were assigned to twice daily or thrice daily milking frequency. Half-sisters were assigned to milking frequency on alternate calvings, and the nonsibling pair was assigned at random. Milk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
3
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 6 publications
9
49
3
3
Order By: Relevance
“…Vale salientar que a realização da terceira ordenha possui como vantagens aumento de produção de leite (Gama e Lopes, 2008), diminuição dos custos fixos, melhor saúde do úbere por maior retirada de contaminantes, aumento no conforto do animal, melhor observação nos casos de mastites, o que melhora o manejo (Amos et al, 1985).…”
Section: Resultados E Discussõesunclassified
“…Vale salientar que a realização da terceira ordenha possui como vantagens aumento de produção de leite (Gama e Lopes, 2008), diminuição dos custos fixos, melhor saúde do úbere por maior retirada de contaminantes, aumento no conforto do animal, melhor observação nos casos de mastites, o que melhora o manejo (Amos et al, 1985).…”
Section: Resultados E Discussõesunclassified
“…In this study, the increase of 16.75% in milk production, by implementing the third milking, was obtained by averaging the estimates reported by several researchers (Vasconcellos, 1975;Amos et al, 1985;Bar-Peled et al, 1995;Erdman & Varner, 1995;Hebert, 2002;Caminha & Gonçalves, 2003;Alves, 2004;Negrão, 2004;Dahl, 2005;Dias, 2005;Gama & Lopes, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies demonstrated the advantages and disadvantages of this practice, including increase in milk production (Amos et al, 1985;DePeters et al, 1985;Bar-Peled et al, 1995;Alves, 2004;Negrão, 2004;Dahl, 2005;Gama & Lopes, 2008;Bernier-Dodier et al, 2010), changes in milk composition (Waterman et al, 1983;Amos et al, 1985;DePeters et al, 1985;Allen et al, 1986;Klei et al, 1997), effect on cow health and reproduction (Jarrett, 1977;Logan et al, 1978;Poole, 1982;DePeters et al, 1985;Allen et al, 1986;Moya et al, 2008) and feed intake and metabolism (Kelly et al, 1998;Smith et al, 2002). However, none addressed the issue of economic viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical response to 3X milking is illustrated in Figure 1, which shows the lactation curves of cows milked 2X or 3X for the entire lactation (re-drawn from Amos et al, 1985). Three-times daily milking increased milk production both at peak and through the entire lactation.…”
Section: Frequent Milking or Suckling Increases Milk Productionmentioning
confidence: 99%